Exploring the Effectiveness of Mobile Smartphones in Teaching Islamic Studies among Senior Secondary Schools - Jibril, Ayuba Olaniyi; Kayode, Abdulkareem Musa (Indonesian Journal of Educational Research and Review, 2023)
The need for Islamic Religious teachers in Senior High Schools to fully integrate ICT tools, especially smartphones, in enhancing effective and efficient teaching in digital processes compared to traditional teaching methods should not be underestimated. This study aims to analyze the integration of ICT mobile smartphones for effective teaching of Islamic studies among senior secondary schools. This study adopted research quantitative method of research. The instrument used for data collection was validated by three experts in Test & Measurement who found it appropriate for this study. A simple random sampling technique was used to select 194 out of 307 senior secondary school teachers of Islamic studies as the sample size of the study. A questionnaire titled "Effective Integration of Mobile Smartphones for Teaching Senior Secondary Schools Questionnaire (EIMSTSSQ)." The reliability of the instrument was determined using the test re-test reliability technique value of the correlation coefficient obtained at 0.87. The findings of the study revealed that senior secondary school teachers of Islamic studies integrate mobile smartphones for effective teaching of Islamic studies. Also, the study revealed that mobile App skills, Internet skills, mobile smartphones literacy skills, technical proficiency, communication skills, creativity skills, organization and time management, flexibility skills and pedagogical knowledge are the skills needed for the integration of mobile smartphones for effective teaching of senior secondary school. The study further revealed that male and female teachers integrate mobile smartphones to enhance the effective teaching of senior secondary school Islamic studies.